Doors and Perception: Fiction vs. Simulation in Games - Aarseth, Espen (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2007)
In this paper, the author outlines a theory of the relationship of fictional, virtual and real elements in games. Not much critical attention has been paid to the concept of fiction when applied to games and game worlds, despite many books, articles and papers using the term, often in the title. Here, it is argued that game worlds and their objects are ontologically different from fictional worlds; they are empirically upheld by the game engine, rather than by our mind stimulated by verbal information. Game phenomena such as labyrinths, moreover, are evidence that games contain elements that are just as real as their equivalents outside the game, and far from equal to the fictional counterparts.